Seasonal and long-term change in the abundance, accumulation and distribution of beach litter within Table Bay, Cape Town, South Africa - Opie, Brandon (Department of Biological Sciences, 2021)
There is growing global concern with regard to the pollution of the world's ocean, particularly by marine debris and plastics. The daily accumulation rates of stranded beach litter were measured at two sites within Table Bay, repeating similar studies from 1994/95 and 2012. Milnerton is a popular recreational beach near the city, while Koeberg is a seldom visited beach in a nature reserve 39 km from the city. Daily sampling was conducted for ten days in winter (August), spring (October) and summer (November-December) 2019. Of the 39 602 items (116.6 kg) sampled in 2019, plastics (including expanded polystyrene) dominated at both sites in terms of numbers (Milnerton: 97.8 %; Koeberg: 98.7%) and mass (Milnerton: 45.2%; Koeberg: 58.9%). The accumulation rates were generally an order of magnitude greater at Milnerton than Koeberg. Plastics were dominated by single-use items (eg: expanded polystyrene clam shells, food wrapping and straws) and Milnerton's composition showed that there was a strong urban influence on the debris. Statistical analyses indicated there were large seasonal differences in accumulation rates at both sites. Milnerton's accumulation rate was ~8 times greater in winter (801.8 items·100 m-1 ·day-1 ) than in spring (97.4 items·100 m-1 ·day-1 ) and summer (86.4 items·100 m-1 ·day-1 ) in 2019. The winter peak was attributed to increased rainfall, which flushed the rivers, and to the reduced cleaning efforts in the catchments in the winter. The marine debris at Koeberg consisted of proportionally more buoyant items than Milnerton, items which can be transported vast distances, and debris at both sites was predominantly of local land-based origin. Across most sample years (1994/95, 2012 and 2019) and seasons (winter, and summer) Milnerton had significantly greater accumulation rates (min winter 1994/95: 286.7 items·100 m-1 ·day-1 to max winter 2019: 801.8 items·100 m-1 ·day-1 ; min summer 2019: 86.4 items·100 m-1 ·day-1 to max summer 2012: 1698.0 items·100 m-1 ·day-1 ) than Koeberg (min winter 2019: 55.9 items·100 m-1 ·day-1 to max winter 1994/95: 129.3 items·100 m-1 ·day-1 ; min summer 2019: 45.7 items·100 m-1 ·day-1 to max summer 2012: 151.4 items·100 m-1 ·day-1 ), attributed to many more sources of debris. Across all sample years, both sites had significantly greater winter accumulation rates than summer. A large decrease was seen in summer at both sites from 2012 to 2019, with a 95% (Milnerton) and 70% (Koeberg) reduction in total accumulation rates. The commencement of municipal cleaning efforts in the catchment areas and along the adjacent beach areas in the spring, which continued into summer, was likely a contributing factor to the decreases. Plastics (including expanded polystyrene) dominated the marine debris composition at both sites across all years and seasons and their proportions at both beaches have increased since 1994/95 from approximately 80 % to 95 %. It is evident that plastics are still prevalent in the environment. Improving waste management facilities and implementing effective cleaning measures throughout the year seem to be effective ways to reduce the marine debris problem. There is a need to shift away from single-use plastic items (such as straws, earbuds and food packaging) and to find more sustainable alternatives.